The medicinal uses of the genus Mahonia in traditional Chinese medicine: An ethnopharmacological, phytochemical and pharmacological review. (4th December 2015) - He, Jian-Ming; Mu, Qing
Abstract: Ethnopharmacological relevance: Plants of the genus Mahonia Nuttall (Berberidaceae) have a long history of medical use in Traditional Chinese Medicine (TCM) for the treatment of a wide range of health disorders, such as tuberculosis, periodontitis, dysentery, pharyngolaryngitis, eczema, and wounds. In the theory of TCM, most Mahonia species exert the effects of relieving internal heat, eliminating dampness, removing toxins, suppressing pain, promoting blood circulation, inhibiting cough and alleviating inflammation. The aim of the review is to provide comprehensive summary on ethnopharmacology, phytochemistry, pharmacology, toxicology and clinical trials of Mahonia species used in TCM based on scientific literature. Available scientific evidence supporting the therapeutic effects of Mahonia species in TCM is demonstrated and opportunities for future research are discussed to highlight the scientific gaps in our knowledge that deserves further investigation. Methods: The available information on the ethnopharmacological uses in Chinese medicine, phytochemistry, pharmacology and clinical practice of the genus Mahonia was collected from Chinese Herbal Classics, published books, un-published resources, dissertations and various worldwide-accepted scientific databases: CNKI, PubMed, ScienceDirect, SpringerLink, Google Scholar, Wiley, TPL (www.theplantlist.org ), SciFinder, and Embase. Results: A variety of ethnomedical usages of Mahonia have been recorded in ancient Chinese books and references. The phytochemical research of this genus has resulted in the identification of more than 150 chemical constituents, among which alkaloids are predominant. The isolated compounds and crude extracts have been shown to exhibit a wide spectrum of in vitro and in vivo pharmacological effects, including antimicrobial, anti-inflammatory, hepatoprotective, antioxidant, antimutagenic and analgesic properties. Preparations containing Mahonia species have been demonstrated to exert good efficacy for the clinical treatment of dysentery, internal and external hemorrhage, acne vulgaris and chronic pharyngitis, among other diseases. Conclusions: The available scientific references demonstrate that the traditional medical uses of some important Mahonia species in TCM have been evaluated in modern pharmacological studies. Isoquinoline alkaloids may contribute to some of the activities shown by the plants of this genus. However, further studies employing scientific technologies and methods are warranted to reveal the phytochemistry of this genus, particularly to detail the active compounds and the underlying mechanisms. Graphical abstract: